Survival of Traditional Retailers: An Islamic Business Perspective - Lilik Rahmawati; Mutimmatul Faidah (al-Uqud : Journal of Islamic Economics, 2020)
This study aimed to explain the reality of survival mechanisms and adaptive strategies by traditional retailers in Surabaya in facing the existence of massive modern retail stores. This study used qualitative research with a phenomenological approach. The data collection method used observation and interview techniques. Data analyzed with Clark and Scott's survival mechanism theory and the adaptive strategy by Miles and Snow. The result of this research was in the aspect of defender strategy, traditional retailers did various strategies when prices went up, and instead of increased the prices they choosed to reduce the profits. The stores equipped with people daily needs to retain customers. Even though the stock was small, the items sold were complete. It was important to promote family relations with buyers. A striking aspect is the close family relation that was so different from modern retail stores. In the aspect of reactor strategy, the owners responded to the situation without having a long-term strategy design. Their stores responses were reactive and short-term oriented in the form of selling goods by following the tastes of buyers and current trends. Meanwhile, in carrying out business performance in connection with the survival mechanism, Surabaya traditional retailers met the business assessment of the Islamic perspective namely on the aspects of material, mental, spiritual, and fraternal.